2013
DOI: 10.1002/ajpa.22255
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 21 and facial developmental instability

Abstract: The most common live-born human aneuploidy is trisomy 21, which causes Down syndrome (DS). Dosage imbalance of genes on chromosome 21 (Hsa21) affects complex gene-regulatory interactions and alters development to produce a wide range of phenotypes, including characteristic facial dysmorphology. Little is known about how trisomy 21 alters craniofacial morphogenesis to create this characteristic appearance. Proponents of the “amplified developmental instability” hypothesis argue that trisomy 21 causes a generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 71 publications
(108 reference statements)
6
31
0
4
Order By: Relevance
“…Although in our sample we were not able to measure asymmetry in all body sites, we noted unilateral cervical ribs in 15.8% of the fetuses and this finding is further support for aneuploidy as a source of increased developmental instability in humans. This is in line with recent work identifying a high rate of limb asymmetry in human aneuploid fetuses and facial asymmetry in trisomy 21 [Starbuck et al, 2013;Bots et al, 2014].…”
Section: Discussionsupporting
confidence: 92%
“…Although in our sample we were not able to measure asymmetry in all body sites, we noted unilateral cervical ribs in 15.8% of the fetuses and this finding is further support for aneuploidy as a source of increased developmental instability in humans. This is in line with recent work identifying a high rate of limb asymmetry in human aneuploid fetuses and facial asymmetry in trisomy 21 [Starbuck et al, 2013;Bots et al, 2014].…”
Section: Discussionsupporting
confidence: 92%
“…Methods for studying fluctuating asymmetry using this approach have been developed [199], but have been used in only relatively few studies [38,39,47,52,68,138,178,200,201]. The vast majority of studies, however, have used Procrustes approaches and this review therefore is focusing mainly on these.…”
Section: Geometric Morphometricsmentioning
confidence: 99%
“…They found that the dental asymmetry of the Down syndrome individuals was nearly twice that of a control population. More recently, Starbuck et al [168] reported 140%-160% greater facial asymmetry in Down syndrome individuals than in normally developing siblings and sibling pairs. Nevertheless, there have been well-designed studies that have found no increase in fluctuating asymmetry with Down syndrome.…”
Section: Genetic Stressorsmentioning
confidence: 99%